PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 011 SIDOREJO KECAMATAN SIMPANG KANAN. - Suriati Berutu; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to inprove the learning outcomes of IPA through coomperative learning model model type thing pair share ( TPS ) in classroom students IV SDN 011 Sidorejo. The subject of this student in the class students IV SDN Sidorejo. Wich was held in 2017 with a total of 24 people 11 male student and 13 female student. The research is a classroom action research (PTK) with 2 cycles conducted on 11 april to 4 may 2017. Research datashows that the learning process has increased. This can be proven on teacher activity scores and student during learning process experiencing dizziness. Cycle 1 meating activity 62,50% with good category increased by 12,5% then the second meeting became 75% with good category. In the second cycle of teacher activity in crased in the first meeting was 8.33% then to 83.37% with very good category. In the second meetimg increased by 8.34% to 91.67% with very good category . while the first cycle activity of the first meeting was 58.33% with sufficient category and increased by 8.33% of the second meeting to 66.67% with good category . in the second cycle of the first meeting of 12.5% to 91.67% with very good . the results of learning obtained from the value of replication before doing research with an average of 58.33% in the first cycle increased to 68.75% and increased in cycle II with and average of 80.00% . based on the result of research can be concluded that with the results of science students learning sdn 011 sidorejo sub districts.Keyword: Model type thing pair share, learning outcomes of IPA